NCR as a biomarker for nutritional status and inflammation in predicting outcomes in patients with cancer cachexia: a prospective, multicenter study - Li, Xiangrui; Deng, Li; Xie, Hailun; Li, Shuqun; Zhao, Hong; Liu, Tong; Liu, Xiaoyue; Lin, Shiqi; Liu, ChengAn; Shi, Han-Ping (BMC cancer, 2025)
Systemic inflammation and nutritional status are key factors affecting the prognosis of patients with cancer cachexia. This study aims to evaluate the prognostic value of a new nutritional and inflammatory index, Prognostic Nutritional CRP Ratio (NCR), in patients with cancer cachexia. This prospective multicenter study analyzed 3,447 patients diagnosed with cancer cachexia across over 40 clinical centers in China, from June 2012 to December 2023. The NCR was calculated as BMI × albumin / CRP. The Cox proportional hazards regression model was utilized to analyze hazard ratios (HRs) for all-cause mortality. The relationship between NCR and all-cause mortality was assessed using restricted cubic spline modeling. The optimal cutoff value for NCR was determined through maximally selected rank statistics. Among the 3,447 individuals diagnosed with cancer cachexia in our study, 2,296 (66.6%) were men, and 1,151 (33.4%) were women. With a median follow-up duration of 45.33 months, the mean age of the participants was 63.8 ± 11.4 years. We observed that lower NCR levels were prevalent among cachexia patients across a spectrum of cancer types, including lung, colorectal, liver, esophageal, breast, ovarian, and cervical cancers. We observed that lower NCR levels were prevalent among cachexia patients across a spectrum of cancer types, including lung, colorectal, liver, esophageal, breast, ovarian, and cervical cancers. This correlation held true across diverse patient subgroups, delineated by gender, age, smoking status, BMI, TNM stage, and tumor types, underscoring the broad applicability of NCR as a prognostic marker. Moreover, our findings highlighted that cancer cachexia patients with higher NCR levels experienced a significantly improved quality of life. The NCR, indicative of nutritional status and inflammation, is associated with reduced all-cause mortality and could be a valuable prognostic marker for patients with cancer cachexia.